(untitled) (Surkhet Journal, 2014)
The study was conducted in two different Garment factory of Kapan VDC of Kathmandu district in June 2013. The respondents of this study were the breast feeding mothers. Main objectives of the study was to find‌ out‌ the‌ knowledge‌ and‌ practice‌ of‌ mothers‌ about‌ breast‌ feeding‌ and‌ its‌ impact‌ on‌ health‌ of‌ infants‌ who were less than six months old. To meet the objective, 100 lactating working mothers were selected by survey method. The study was based on exploratory and descriptive research and Interview schedule, and anthropometric measurement tool were developed to get necessary information. Among the respondents, only 32% were found delivered at home though the hospitals were very near from their residence. Among the respondents, only 64% fed colostrums to their babies after birth though 71% of them were aware of the importance of colostrums feeding. All most all the respondents of this study belonged to working class families where 82% elder children were the care takers of infants at home and factory premises. Among the infants, 46% were found perfectly healthy, 32% on the borderline, and rest were found in malnutrition condition. Within the six month period to study time, 68% infants were suffered from diarrhea, 28% ARTI, and rest 33% with other health problems.